Assessing Islamic Character in Elementary School Students: A Multi-Source Educational Management Framework - Rustam; Ilham; Syarifuddin; Ade S. Anhar; Muhammad Iqbal (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
Islamic character assessment in elementary schools presents challenges that are at once psychometric and managerial. Curriculum mandates have grown stronger, from the National Education System Law to the Merdeka Curriculum and its Pancasila Student Profile, yet school practice remains impression-based and weakly evidenced. The gap addressed here is the absence of a framework that joins assessment methods, bias mitigation, and educational management into a design that a school can actually run. This conceptual-analytic article synthesises literature on educational assessment, affective measurement, psychometrics, and Islamic educational management to develop a multi-source assessment framework for the primary level. Islamic character is operationalised into three dimensions, namely ubudiyah, personal akhlak, and social akhlak. The analysis shows that assessment methods are systematically complementary rather than hierarchically ordered, and that most threats to validity originate in organisational conditions, not in the instrument. The proposed model triangulates evidence across teachers, parents, and students, and is delivered through three implementation packages calibrated to differing levels of school capacity. The article contributes a design in which managerial feasibility is treated as a precondition of validity rather than a concession against it. Its limitation is that the framework has not been empirically tested; subsequent work should establish content validity, inter-rater reliability, and the managerial conditions under which the packages are sustained.